Young Women's Continuance Intentions to use Communication and Social Media Apps - Gadhiya, Palak; Panchal, Nilam (Indian Journal of Marketing, 2021)
The rapid adoption of smartphones in the last few years indicates the changing scenario of communication patterns. The mobile app market is taking prime space in the digital world with high adoption and year-on-year growth rate. Out of all the categories, social media and communication (instant messaging apps) consume more than half of the digital time in most of the countries across the world. Generally, men and women have different patterns for preferences and usage of any particular thing. Similarly, preferences for mobile applications and usage styles also differ amongst them. Literature supports the fact that the usage of mobile apps among women is high compared with men. Thus, this study focused on the impact of satisfaction and attitude on the continuance intention of usage for communication and social media apps among young women. A hypothesized model was developed by the authors to find out the impact of perceived usefulness, enjoyment, and confirmation of expectations on satisfaction and attitude for the continuance usage of communication and social media apps. The data were collected by circulating the questionnaire on online and offline platforms. A total of 263 respondents from four different regions of Gujarat were considered for the analysis, and model validation was done by adopting the structural equation modelling method. The results confirmed that satisfaction was the strongest predictor for the continuance usage of communication and social media apps led by perceived usefulness and confirmation of expectations, while attitude significantly affected continuance usage led by perceived enjoyment.